Mineral nutrient composition of leaves and fruits of black table Olive cv. Gemlik - Başar, Haluk; Gürel, Serhat (Bangladesh Journal of Botany, 2018)
A comparative study on mineral composition of the olive trees was made to see the changes in the content of the nutrient elements in the component (leaf and fruit) parts. Differences between the leaf and fruit mean concentrations of the whole elements examined were found to be statistically significant. Potassium and boron concentrations in the fruits were higher than that of the leaves. But, the concentration of the rest of the elements in the fruits was lower than the leaves.